Combined effect of high pressure and vinegar addition on the control of Clostridium perfringens and quality in nitrite-free emulsion-type sausage. (March 2019) - Lee, Sang Hui; Choe, Juhui; Shin, Dong Jin; Yong, Hae In; Choi, Yukyung; Yoon, Yohan; Jo, Cheorun
Abstract: We evaluated the combined effect of high pressure (HP) and vinegar addition on control of Clostridium perfringens and quality in emulsion-type pork sausages. Sausages were manufactured with different levels of commercial white distilled vinegar made with jasmine tea extract (0, 1, and 2%) and sodium nitrite (0.02%, control). The sausages except for sodium nitrite treatment were subjected to HP at 500 MPa (four cycles and each for 3 min). After storage, the combined treatment of HP and vinegar showed the lowest number of C . perfringens vegetative cells (4.8-log CFU/g reduction) among the all treatments. The combined treatment also inhibited the growth of C . perfringens spores for five weeks (stored at 4 °C for two weeks followed by at 20 °C for three weeks). Among all treatment combinations, the best pH, water-holding capacity and chewiness, were found with the HP-vinegar sausage. In addition, vinegar treatment inhibited the lipid oxidation of sausage throughout the storage. Use of HP and vinegar addition inhibited growth of C . perfringens without observed adverse effects on quality of the emulsion-type sausage. Industrial relevance: Currently, the use of natural additives and novel processing technologies for replacing sodium nitrite in meat products is gaining attention owing to increase in consumer demand for nitrite-free and safe meat products. The study showed that the addition of 1% (w/v) of vinegar and pressure treatment at 500 MPa (four cycles and each for 3 min) can replace sodium nitrite to inhibit growth of C . perfringens in emulsion-type sausages. Highlights: Vinegar supplemented sausages (0, 1, 2%) were subjected to HP (0.1, 500 MPa) and stored for 5 weeks. Vegetative cells and spores of C. perfringens in 1% vinegar-HP sausages were reduced by 4.8 and 2.8 log CFU/g, respectively. No significant quality changes were observed in the sausage with HP (500 MPa for 12 min) and vinegar (1%). HP and vinegar can be applied for safer nitrite-free sausage against C . perfringens with acceptable quality.